2020
DOI: 10.1186/s13223-020-00438-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MP-AzeFlu enhanced by activation of bitter taste receptor TAS2R

Abstract: MP-AzeFlu is relatively new a pharmaceutical drug used in the treatment of allergic rhinitis. It is comprised of azelastine hydrochloride (AZE), a potent histamine-H1-receptor antagonist and fluticasone propionate (FP), corticosteroid. It's somewhat bitter taste (often considered a disadvantage) can be attributed to AZE. We here hypothesize that MP-AzeFlu may induce some of its beneficial effects through activation of bitter taste receptors (Tas2R), which have recently been described in human airways. In the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…TAS2R was found to be expressed in hDPSCs for the first time. TAS2R was initially identified in taste buds of the tongue and played a role in recognizing bitter taste, preventing the ingestion of toxic substances and performing self-defense functions [ 32 ]. There is increasing evidence that TAS2R has a variety of functions independent of taste in anti-inflammation [ 16 ], anti-infection [ 14 ], reduction airway hyper-responsiveness [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…TAS2R was found to be expressed in hDPSCs for the first time. TAS2R was initially identified in taste buds of the tongue and played a role in recognizing bitter taste, preventing the ingestion of toxic substances and performing self-defense functions [ 32 ]. There is increasing evidence that TAS2R has a variety of functions independent of taste in anti-inflammation [ 16 ], anti-infection [ 14 ], reduction airway hyper-responsiveness [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“… 65 Upon investigation towards the mechanism of MP-AzeFlu, Ekstedt et al (2020) discovered that the dilatory effects of MP-AzeFlu were independent of the common airway dilatory pathways involving histamine receptors (H1-, H2- and H3-), prostaglandins, cAMP and cGMP. 66 When examining pre-contracted murine airways, the authors found that MP-AzeFlu and AZE had dilatory effects similar to that of T2R agonists, suggesting that MP-AzeFlu functioned through bitter taste receptor activation.…”
Section: Potential For Drug Developmentmentioning
confidence: 99%
“…The interest in T1Rs and T2Rs is mainly because of their quick immune response (e.g., against inhaled harmful substances and their second messenger pathways that take a few seconds to minutes to be expressed) compared to other receptors expressed on the epithelium [ 50 , 72 , 73 ]. Activation of T2Rs using bitter taste agonists have been adopted to treat inflammation-linked respiratory diseases such as asthma, chronic obstructive pulmonary disease, CRS, and allergic rhinitis [ 47 , 69 , 74 , 75 ]. In addition, the T1R attenuation of T2R mediated anti-microbial peptide secretion may also have important clinical relevance.…”
Section: Clinical Application Of Taste Receptors For the Airwaysmentioning
confidence: 99%
“…Allergic rhinitis is a chronic airway disorder, clinically characterized by sneezing, nasal discharge, nasal obstruction, and nasal hyperreactivity [ 53 ]. In the study of Ekstedt et al, the authors investigated the involvement of T2Rs in the beneficial effect of MP-AzeFlu in the pre-contracted airway of Balb/c mice [ 75 ]. MP-AzeFlu is a drug used in the treatment of allergic rhinitis patients and consists of azelastine hydrochloride (AZE) and fluticasone propionate (FP).…”
Section: Clinical Application Of Taste Receptors For the Airwaysmentioning
confidence: 99%
See 1 more Smart Citation